2013
DOI: 10.1158/1078-0432.ccr-13-0799
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response to Neoadjuvant Chemotherapy Among 7 Triple-Negative Breast Cancer Molecular Subtypes

Abstract: Purpose The clinical relevancy of the 7-subtype classification of triple-negative breast cancer (TNBC) reported by Lehmann and Bauer et al is unknown. We investigated the clinical relevancy of TNBC heterogeneity by determining pathological complete response (pCR) rates after neoadjuvant chemotherapy, based on TNBC subtypes. Experimental Design We revalidated the Lehmann and Bauer et al. experiments using Affymetrix CEL files from public datasets. We applied these methods to 146 TNBC patients with gene expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
542
4
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 632 publications
(588 citation statements)
references
References 23 publications
19
542
4
8
Order By: Relevance
“…More recently, the subtyping of three large clinical trials (MA.5 [Levine et al, 2005], GEICAM/9906 [Martín et al, 2008] and MA.12 [Bramwell et al, 2010]) using the PAM50 qRT-PCR based assay showed that approximately 30% of TNBC identified by central pathology review do not fall under the BL subtype category (Cheang et al, 2012). Lately, Lehmann et al (2012) and Masuda et al (2013) have reported that TNBC can be classified into 7 subtypes (6 defined subtypes and an unstable group) by gene expression microarray. The subtypes were characterized as BL 1, BL 2, immunomodulatory, mesenchymal, mesenchymal stem-like, luminal androgen receptor and unstable.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the subtyping of three large clinical trials (MA.5 [Levine et al, 2005], GEICAM/9906 [Martín et al, 2008] and MA.12 [Bramwell et al, 2010]) using the PAM50 qRT-PCR based assay showed that approximately 30% of TNBC identified by central pathology review do not fall under the BL subtype category (Cheang et al, 2012). Lately, Lehmann et al (2012) and Masuda et al (2013) have reported that TNBC can be classified into 7 subtypes (6 defined subtypes and an unstable group) by gene expression microarray. The subtypes were characterized as BL 1, BL 2, immunomodulatory, mesenchymal, mesenchymal stem-like, luminal androgen receptor and unstable.…”
Section: Discussionmentioning
confidence: 99%
“…12 Responses to neoadjuvant chemotherapy are also different, with basallike 1 having the highest complete pathologic response rate (52%) and basal-like 2 and luminal androgen receptor tumors having the lowest complete pathologic response rates (0% and 10%, respectively). 114 Triple negativity is the most commonly used IHC surrogate for basal-like tumors. 11 Immunohistochemical analysis of BLBC cases that had been defined by GEP demonstrated that added IHC testing for CK5/6 and EGFR was better able to define this subtype than triple negativity alone.…”
Section: Triple-negative Breast Cancermentioning
confidence: 99%
“…53 Retrospective trials have found that molecular profiles of TNBC have clinical utility in predicting chemotherapy response. 29,54 In a clinical research of 1055 patients with TNBC, BLBC or both, only when TNBC can be stratified into BLBC subtype could patients be identified with notably better response after chemotherapy. 55 Previous studies show that BLBC harbors the hallmarks of BRCAness.…”
Section: Molecular Subtype Associated Biomarkersmentioning
confidence: 99%